(untitled) (Docentes 2.0 Journal, 2024)
At a global level, leadership forms an important part of organizations, promoting the coordination, organization, control, and direction of processes and procedures to obtain expected results. The research objective was to determine managerial leadership’s influence on the educational quality of Educational Institutions (II.EE) in Latin America in the last ten years. The research was based on the deductive positivist paradigm, with a qualitative approach, non-experimental design, and descriptive type. The population was made up of 15 documents from 2010 to 2020. The methodology applied is the content analysis technique and the registration table instrument. The result was the collection of 15 scientific articles that considered managerial leadership important for II.EE also influences educational quality, promoting students to have better academic performance. Regarding the discussion, they agree and mention that managerial leadership is essential for educational institutions because they are responsible for making decisions regarding the situation or panorama. Therefore, its relationship with educational quality is significant since it promotes learning. Educational institutions need a dynamic design to strengthen quality and prepare teachers for optimal teaching. Finally, it is concluded that managerial leadership has significantly influenced educational quality in II—EE in Latin America in the last ten years.